2014
DOI: 10.1097/mib.0000000000000172
|View full text |Cite
|
Sign up to set email alerts
|

IFNG rs1861494 Polymorphism Is Associated with IBD Disease Severity and Functional Changes in Both IFNG Methylation and Protein Secretion

Abstract: Background Mucosal expression of IFN-γ plays a pivotal role in IBD pathogenesis and IBD-risk regions flank IFNG. The conserved IFNG rs1861494 T/C, introduces a new CpG methylation site, and is associated with disease severity and lack of therapeutic response in other infectious and immune mediated disorders, and is in linkage-disequilibrium with a UC disease severity region. It seems likely that CpG-altering SNPs modify methylation and gene expression. This study evaluated the association between rs1861494 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…In the present study, we investigated the relationship between IFN-γ rs1861494 polymorphism and IgAN, and report that the IFN-γ rs1861494 polymorphism is associated with IFN-γ serum levels. This is in line with the results that T allele of rs1861494 in IFNG gene in patients with IBD correlated with elevated expression of IFN-γ [37]. …”
Section: Discussionsupporting
confidence: 78%
“…In the present study, we investigated the relationship between IFN-γ rs1861494 polymorphism and IgAN, and report that the IFN-γ rs1861494 polymorphism is associated with IFN-γ serum levels. This is in line with the results that T allele of rs1861494 in IFNG gene in patients with IBD correlated with elevated expression of IFN-γ [37]. …”
Section: Discussionsupporting
confidence: 78%
“…43,44 Furthermore, genome-wide association studies linked SNPs around the IFNG locus and enhanced IFNG expression with IBD. 45,46 Certain bacteria promote specific T-cell responses, e.g., SFB drive the development of Th17 cells. 47 Likewise, specific bacteria in healthy mice might suppress the induction of Th1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al reported that although IFN‐γ rs1861494 polymorphism could influence serum IFN‐γ level, there was no obvious association between the SNP with immunoglobulin A nephropathy (IgAN) in Chinese Han population 27 . However, the study scheduled by Gonsky et al reported that IFN‐γ rs1861494 polymorphism could influence inflammatory bowel disease severity via its functional roles in IFN‐γ gene methylation and protein secretion among Caucasian population 19 . The divergences might be attributed to the relative small sample size, different study populations and geographic regions, as well as the diverse aetiologies of the study diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A related case‐control study reported that IFN‐γ rs2430561 polymorphism may contribute to risk of AS via influencing IFN‐γ expression 20 . Rs2069727 and rs1861494 are two common polymorphisms in IFN‐γ gene, and both of them have the possibility to influence production of IFN‐γ protein 19,21 . According to the previous researches, we hypothesized that IFN‐γ r s2069727 and rs1861494 polymorphisms might be involved in AS.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation